BIRTH CONTROL IN BELARUS AND CHINA: CURRENT POLICY - BOBROVA, Anastacia; PILIUTSIK, Andrei; YUAN, Gao (Economy and Sociology, 2021)
Belarus and China are experiencing a decline of the total fertility rate (TFR). On the one hand, this was a natural response to the increasing role of women in society, on the labor market and increasing women’s participation in education. As a result women are marrying and have children later in their life, which leads to a decrease in the number of children born. On the other hand, scientists state the role of the policy on childbearing, the strength of which is difficult to calculate although. Today, one can observe a rapid strengthening of bilateral relations in economic, social and other areas of regulation. Belarus and China had different birth control vectors. In the conditions of protracted depopulation in the Republic of Belarus, stimulation of the birth rate has become a priority goal of the state policy. Rapid population growth in China posed a threat to economic, food, and even environmental security. This led to the adoption of drastic measures to limit the number of children born in Chinese families. This paper focuses on how similar are birth control policies in Belarus and China. The choice of countries is also due to the fact that today both countries set the goal to stabilize the population in order to ensure sustainable economic development and improvement in the quality of life. The paper presents a description and analysis of legal acts that regulate demographic processes, as well as specific areas of support for families with children. It was revealed that Belarus provides multilateral (mostly financial) assistance not only for the birth of a child, but also for his upbringing. The system is designed so that a woman cares for a child 3 years after his birth. In China, in the face of fierce competition in the labor market, women go to work after maternity leave. They are forced to use the services of pre-school education, even if they are expensive. As a result, the decision to give birth to a child is weighed in terms of the economic possibilities of families. In China, measures may vary depending on the territory; in Belarus, politics is one for all. It is difficult to assess in which country the policy is more effective. The total fertility rate for the past 25 years is very similar.